Converse flexoelectric effect in comb electrode piezoelectric microbeam - Shen, Zhiyuan (2013)
We demonstrate the converse flexoelectric effect in a lead zirconate titanate microbeam. The fringe electric field of a comb electrode induces converse flexoelectric responses in uniformly poled and depoled beams. The simulated electric field distribution shows that bending of the beam is induced by piezoelectric and μ11, μ12 flexoelectric coefficients. Simulations indicate that piezoelectric displacement occurs in different directions in the two opposite poled samples while flexoelectric displacement remains the same. This finding is verified by the displacement measurement results.